Pengaruh Profitability, Leverage, dan Firm size terhadap Tax avoidance dengan Sales growth sebagai Variabel Moderasi - Abestian, Geovan Isnaen; Yuliafitri, Indri (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2025)
This study aims to examine the effect of profitability, leverage, and firm size on tax avoidance, as well as to analyze the role of sales growth as a moderating variable. Tax avoidance is often employed as a legal strategy by companies to minimize tax burdens, however it also poses fiscal risks and may reflect weak tax compliance. This research adopts a quantitative approach, focusing on mining sector companies listed on the Indonesia Stock Exchange (IDX) during the 2020–2024 period. The sample was selected using a purposive sampling method, resulting in 21 companies that met the criteria, with a total of 105 observations. Data were analyzed using Moderated Regression Analysis (MRA) based on panel data, processed with the assistance of EViews 12 software. The findings reveal that profitability has a significantly negative effect on tax avoidance, while leverage and firm size exhibit significantly positive effects. Furthermore, sales growth is found to strengthen the effect of leverage on tax avoidance, but does not moderate the relationship between profitability or firm size and tax avoidance.